Impact ionization coefficients in 4H-SiC by ultralow excess noise measurement - Green, James E. (2013)
Photomultiplication and excess noise measurements have been undertaken on two 4H-SiC avalanche photodiodes (APDs) using 244-nm light and 325-nm light. The structures are APDs with separate absorption and multiplication regions having multiplication regions of 2.74 and 0.58 μm , respectively. Pure injection conditions in the thicker device permit the measurement of pure-hole-initiated photomultiplication and an excess noise factor. Ionization coefficients for both carrier types have been extracted from these data using a local model. The use of the excess noise factor to infer the value of the less readily ionizing coefficient α from pure hole injection measurements is more robust than direct extraction from mixed injection measurements. This is because mixed injection introduces uncertainty in the generation profile. We report a significant reduction of the electron ionization coefficient α at low fields. The more readily ionizing hole coefficient β remains very similar to prior work.